An Analysis of Endocannabinoid Concentrations and Mood Following Singing and Exercise in Healthy Volunteers - Stone, Nicole L.; Millar, Sophie A.; Herrod, Philip J. J.; Barrett, David A.; Ortori, Catharine A.; Mellon, Valerie A.; O’Sullivan, Saoirse E. (Frontiers in Behavioral Neuroscience, 2018)
The euphoric feeling described after running is, at least in part, due to increased circulating endocannabinoids. Endocannabinoids are lipid signalling molecules involved in reward, appetite, mood, memory and neuroprotection. The aim of this study was to investigate whether activities other than running can increase circulating endocannabinoids. 9 healthy female volunteers (mean 61 yrs) were recruited from a local choir. Circulating endocannabinoids, haemodynamics, mood and hunger ratings were measured before and immediately after 30 min of dance, reading, singing or cycling in a fasted state. Singing increased plasma levels of anandamide (AEA) by 42% (P<0.05), palmitoylethanolamine (PEA) by 53% (P<0.01) and oleoylethanolamine (OEA) by 34% (P<0.05), and improved positive mood and emotions (P<0.01), without affecting hunger scores. Dancing did not affect endocannabinoid levels or hunger ratings, but decreased negative mood and emotions (P<0.01). Cycling increased OEA levels by 26% (P<0.05) and tended to decrease how hungry volunteers felt, without affecting mood. Reading increased OEA levels by 28% (P<0.01) and increased the desire to eat. Plasma AEA levels were positively correlated with how full participants felt (P<0.05).Plasma OEA levels were positively correlated with positive mood and emotions (P<0.01). All three ethanolamines were positively correlated with heart rate (P<0.0001). These data suggest that activities other than running can increase plasma endocannabinoids associated with changes in mood or appetite. Increases in endocannabinoids may underlie the rewarding and pleasurable effects of singing and exercise, and ultimately some of the long-term beneficial effects on mental health, cognition and memory.